2021
DOI: 10.1021/acsabm.1c00563
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Based Ionic-Liquid-Mediated Nanodispersions as Biocompatible Carriers for the Enhanced Transdermal Delivery of a Peptide Drug

Abstract: Lipid-based biocompatible ionic liquids (LBILs) have attracted attention as carriers in transdermal drug delivery systems (TDDSs) because of their lipophilic character. In this study, we report the formulation of a peptide−LBIL complex microencapsulated in an oil phase as a potential carrier for the transdermal delivery of leuprolide acetate as a model hydrophilic peptide. The peptide−LBIL complexes were prepared via a water-in-oil emulsion composed of 1,2-dimyristoyl-sn-glycerol-3-ethyl-phosphatidylcholine (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…F-C18:2 facilitated the permeation of more insulin than other SAIL-based MEFs because of the double π-bond in its anion structure. It has been reported that ILs and IL-based formulations can facilitate the permeation of drugs, proteins, and peptides because of their ionic character and ability to extract SC lipid. , It has also been reported that the presence of one or more π-bonds in the IL structure increases the hydrophobicity of the IL, resulting in greater reduction of the barrier function. , The presence of double bonds in unsaturated FAs enables the lipid structure to bend or kink, allowing successful permeation through the skin. Because it has more double bonds than the other SAILs investigated, [Chl]­[C18:2] is able to increase the permeation more by creating greater fluidity or more kinks in the lipid structure of the skin. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…F-C18:2 facilitated the permeation of more insulin than other SAIL-based MEFs because of the double π-bond in its anion structure. It has been reported that ILs and IL-based formulations can facilitate the permeation of drugs, proteins, and peptides because of their ionic character and ability to extract SC lipid. , It has also been reported that the presence of one or more π-bonds in the IL structure increases the hydrophobicity of the IL, resulting in greater reduction of the barrier function. , The presence of double bonds in unsaturated FAs enables the lipid structure to bend or kink, allowing successful permeation through the skin. Because it has more double bonds than the other SAILs investigated, [Chl]­[C18:2] is able to increase the permeation more by creating greater fluidity or more kinks in the lipid structure of the skin. , …”
Section: Resultsmentioning
confidence: 99%
“…29,49 It has also been reported that the presence of one or more π-bonds in the IL structure increases the hydrophobicity of the IL, resulting in greater reduction of the barrier function. 52,56 The presence of double bonds in unsaturated FAs enables the lipid structure to bend or kink, allowing successful permeation through the skin. Because it has more double bonds than the other SAILs investigated, [Chl][C18:2] is able to increase the permeation more by creating greater fluidity or more kinks in the lipid structure of the skin.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These formulations (especially the L-proline ethyl ester linoleate-based one), enhanced the percutaneous permeation of an antigenic peptide accross porcine skin [ 168 ]. The same authors have very recently used similar fatty acid-based ILs to formulate IL-in-oil nanodispersions that were optimized for higher physicochemical stability, as well as increased loading capacity and in vivo transdermal delivery of the anticancer nonapeptide leuprolide [ 169 ]. The nanodispersions showed no significant toxicity both in vitro and in vivo, and peptide transdermal delivery could be enhanced by as much as 65-fold compared with the aqueous delivery vehicle [ 169 ].…”
Section: Ionic Liquid-based Approaches In Dermal and Transdermal Drug Deliverymentioning
confidence: 99%
“…33 In a previous study, we developed a formulation for transdermal peptide delivery that comprised an LBIL-biocompatible surfactant and Span 20 as a co-surfactant. 8 The LBIL-mediated formulation significantly enhanced topical and transdermal peptide delivery compared with the aqueous formulation. An LBIL plays the pivotal role of increasing the bioavailability and pharmacokinetics parameters of a peptide compared with an aqueous subcutaneous injection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24 [Glu] were used to increase the TDD of caffeine and salicylate. 25 Our group reported the effective transdermal delivery of acyclovir, 26 leuprolide acetate, 8 curcumin, 27 insulin, 28 and paclitaxel 29 using ILs as solubilizing agents/solvents as well as skin permeation enhancers. In such systems, an IL plays the key role of increasing the penetration and permeation of therapeutic agents into/across the skin through the noninvasive disruption of the lipid bilayers of the SC.…”
Section: ■ Introductionmentioning
confidence: 99%